Comparing the performance of four macrophytes in bacterial assisted floating treatment wetlands for the removal of trace metals (Fe, Mn, Ni, Pb, and Cr) from polluted river water. (March 2020) - Shahid, Munazzam Jawad; Ali, Shafaqat; Shabir, Ghulam; Siddique, Muhammad; Rizwan, Muhammad; Seleiman, Mahmoud F.; Afzal, Muhammad
Abstract: Here we compared the performance of four macrophytes namely Brachia mutica, Typha domingensis, Phragmites australis and Leptochala fusca, in bacterially assisted floating treatment wetlands (FTWs) for the clean-up of five trace metals (Fe, Mn, Ni, Pb, and Cr) from polluted river water. The river water was artificially spiked with reagent grade chemicals to increase the trace metal pollution. The macrophytes were planted in a polystyrene sheet to prepare FTWs, which were placed over the metal-contaminated river water. The consortium of five rhizospheric and endophytic bacterial strains, i.e., Aeromonas salmonicida, Pseudomonas indoloxydans, Bacillus cerus, Pseudomonas gessardii, and Rhodococcus sp., was inoculated support the natural remediation ability. We found a significant reduction in the metal content by all four macrophytes and the removal was significantly enhanced when bacterial inoculum was applied. The maximum removal was observed in FTWs planted with P. austra lis and inoculated with bacteria. In this treatment (T6) the Fe, Mn, Ni, Pb and Cr contents were reduced to 0.53, 0.20, 0.09, 1.04 and 0.07 mg L −1 after five weeks retention time. The bacterial inoculation sufficiently increased the plant biomass. All macrophytes depicted potential to uptake and translocate trace metals in the roots instead of shoots. The bacterial inoculation acclimatize the plants roots followed by shoots and enhanced the uptake of metals by macrophytes. This study emphasized the usefulness of macrophytes-bacteria mutualism in FTWs system for the remediation of trace metals. The similar systems may provide practical solutions for the remediation of trace metals of polluted river water. Highlights: Floating treatment wetlands system, augmented with bacteria is an emerging technology for remediation of trace metals The bacteria inoculation in FTWs enhanced the phytoremediation potential of all four macrophytes. All four macrophytes showed potential to uptake and translocate the trace metals in the roots instead of shoots. The phytoremediation potential of P. australis was better than all other macrophytes. Macrophytes-bacteria mutualism is a viable option for remediation of trace metals.